The influence of intermittent altitude exposure to 4100 m on exercise capacity and blood variables - Lundby, C.; Nielsen, T. K.; Dela, F.; Damsgaard, R. (Scandinavian Journal of Medicine & Science in Sports, 2005)
This study was performed to investigate the effects of intermittent hypoxic exposure on blood and exercise parameters. Eight sea level residents were exposed to 2 h daily stimulus to 4100 m altitude in a hypobaric chamber for a total of 14 days. Exercise performance was evaluated at sea level before and after the hypoxic stimulation. Blood samples were obtained before, during, and at time points up to 14 days after the hypoxic exposure. No changes were observed in haemoglobin, haematocrit, reticulocytes, serum transferrin receptors, or EPO levels in the blood. Submaximal cycle (150 W) ergometer exercise corresponded to a oxygen uptake of 1.9±0.1 and 1.9±0.1 L min1 before and after the intermittent altitude exposure, respectively. At maximal exercise the workloads attained were 343±17 and 354±27 W before and after the exposure, with corresponding oxygen uptakes of 4.0±0.2 and 4.2±0.2 L min1. It is concluded that intermittent hypoxic exposure to 4100 m altitude for 2 h daily and a total of 14 days does not affect exercise capacity.